OPTIMIZATION BY 32 FACTORIAL DESIGN AND COMPONENT SCREENING OF MICONAZOLE NITRATE NANOEMULSION. - SHINDE P. B. (International Journal of Pharma and Bio Sciences, 2013)
The objective of the present investigation was to develop and evaluate nanoemulsion for the vaginal delivery of Miconazole nitrate(MCZ). The solubility of MCZ in oils and surfactants was evaluated to construct ternary phase diagram by detecting the area for preparation of nanoemulsion and its optimization done by 32 factorial design using dx-8 trial version software. The formulations that passed thermodynamic stability tests were characterized for pH, refractive index, viscosity, droplet size, drug content, transmission electron microscopy, stability study and in vitro drug release. The MCZ nanoemulsion exhibited globule size of 22nm and polydispersity index of 0.98. A significant increase in drug release, and good in vitro antifungal efficacy were observed in optimized nanoemulsion formulation FM4 which consist of 1%wt/wt MCZ, 20%wt/wt Captex200EP, 40% wt/wt Twen80:CapmulMCM(2:1) and 40% wt/wt distilled water & In vitro antifungal efficacy of formulation FM4 showed a significant increase in percent inhibition when compared with MCZ cream.